POLA KOMUNIKASI KETUA KELOMPOK TANI HUTAN II (KTH II) KEPADA ANGGOTANYA DI KAMPUNG CITIIS DESA MEKARJAYA KECAMATAN ARJASARI BANJARAN KABUPATEN BANDUNG - Amin, Amin; Kustiman, Erwin; Habib, Mohd Nadzrizal; Tiaralivia, Nathasya (Komunitas Manajemen Kompetitif, 2024)
Communication patterns are defined as forms or patterns of relationship between two or more people in the process of sending and receiving in the right way so that the message in question can be understood by the communicant (KTH members). The Forest Farmer Group is a group of farmers who work on gardens or forest land owned by Perhutani. Effective communication within the Forest Farmers Group (KTH) II Kampung Citiis is crucial. However, farmers' ignorance about effective communication patterns is a major obstacle. Therefore, the priority issue is counseling and training with an effective communication pattern system between the Chair of KTH II and members of KTH II Kampung Citiis, which requires a deep understanding of the need for interpersonal communication in agriculture as well as strategies to overcome the ignorance of forest farmers so that messages related to agriculture can be conveyed and understood well by all KTH members. The most effective communication is communication when it is able to change someone's attitude, opinion or behavior dialogically and this can be done between the Extension Officer and the farmers, not depending on how big the quantity is but how big the quality is. Based on the problems that have been identified with partners, there is an agreement to determine priority problems for which immediate solutions will be sought, with the aim of Agricultural Extension and Training which prioritizes how to plant horticulture, coffee and protect forests. Apart from that, efforts are explained to find out the differences and similarities between good and correct planting techniques. There are three activity methods used by the team, namely the directing method, mentoring method and facilitation. The research method in this study uses a descriptive-explanatory research type, namely describing and explaining efforts to find out the differences and similarities in good and correct planting techniques, including fertilization, treatment and plant maintenance, while the data analysis techniques used in this research include interview transcripts, data reduction, analysis, data interpretation and triangulation.